WTO Dispute Settlement: An Economic Analysis of four EU-US Mini Trade Wars - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2004)
Since its inception in 1995, more than 312 disputes have been raised under the WTO Dispute Settlement System. Despite the obvious success of this system, several shortcomings call for a revision under the auspices of the Doha Development Round. With a computable general equilibrium model we analyze the four most prominent trade disputes between the EU and the USA, which we call "mini trade wars": the Hormones, the Bananas, the Foreign Sales Corporations and the Steel cases. The economic analysis revealed several flaws and peculiarities: As a rule, retaliatory tariffs are detrimental to welfare of the retaliating country and amount to "shooting oneself in the foot". Trade wars can only be won by large countries. The WTO arbitrator's estimation of the trade loss in case of non-compliance never translates into equivalent damage to economic welfare. A mechanism to control the collection of retaliatory tariff revenues is missing as is a system to compensate the firms suffering the damage. The major conclusion therefore is that tariffs are very bad instruments for countermeasures. The sanctions mechanism of the Dispute Settlement System should be improved, maybe based on a mechanism of direct transfers.
Keywords: F13; D58; 330; WTO Dispute Settlement; Trade Policy; CGE Model Simulation; WTO-Recht; Internationale Schiedsgerichtsbarkeit; Handelskonflikt; Wirkungsanalyse; Allgemeines Gleichgewicht; Wohlfahrtsanalyse; Theorie; USA; EU-Staaten